It's the talk: a study of involvement initiatives in secure mental health settings. (7th July 2014) - McKeown, Mick; Jones, Fiona; Wright, Karen; Spandler, Helen; Wright, Joanna; Fletcher, Holly; Duxbury, Joy; McVittie, Jolene; Simon,; Turton, Wayne
Abstract: Background: A study of involvement initiatives within secure mental health services across one UK region, where these have been organized to reflect alliances between staff and service users. There is little previous relevant international research, but constraints upon effective involvement have been noted. Objective: To explore and evaluate involvement initiatives in secure mental health settings. Design: A case study design with thematic analysis of qualitative interviews and focus groups. Setting and participants: Data collection was carried out between October 2011 and February 2012 with 139 staff and service users drawn from a variety of secure mental health settings. Findings: Our analysis offers four broad themes, titled: safety and security first?; bringing it all back home; it picks you up; it's the talk. The quality of dialogue between staff and services users was deemed of prime importance. Features of secure environments could constrain communication, and the best examples of empowerment took place in non‐secure settings. Discussion: Key aspects of communication and setting sustain involvement. These features are discussed with reference to Jurgen Habermas's work on communicative action and deliberative democracy. Conclusions: Involvement initiatives with service users resident in secure hospitals can be organized to good effect and the active role of commissioners is crucial. Positive outcomes are optimized when care is taken over the social space where involvement takes place and the process of involvement is appreciated by participants. Concerns over risk management are influential in staff support. This is germane to innovative thinking about practice and policy in this field.